PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PELANGGAN PT PEGADAIAN (PERSERO) CABANG BATAM - Pandiangan, Nova Ria; santoso, Teguh Iman (LPPM Universitas Putera Batam, 2019)
In financial service institutions there are two, namely banks and no banks, non-bank institutions are very useful for the benefit of people who want to borrow money at very low interest, the condition of doing credit if the community has goods to be guaranteed to PT Pegadaian (Persero) Batam Branch. The quality of services and facilities is something that must be maintained and continuously improved by PT Pegadaian for customer satisfaction, because the quality of services and good facilities will make people happy to use services offered by PT Pegadaian (Persero) Batam Branch. This research was conducted to determine the effect of the quality of services and facilities on customer satisfaction at PT Pegadaian (Persero) Batam Branch. In this study the sampling method uses a porposive sampling technique because in a porposive sampling technique, which criteria are made into samples because not all criteria are made as samples. The method in this study is descriptive analysis using primary data and using a questionnaire to find out the results of respondents' responses to the quality of service, facilities and satisfaction felt by customers when using the services of PT Pegadaian (Persero) Batam Branch. The sample in this study were 392 respondents and the scale of measurement using the Likert Scale, and testing data using SPSS 20 and the results of the hypotheses obtained were that service quality had a significant effect on customer satisfaction, facility variables had a significant effect on customer satisfaktion, and together sevice variables and facilities have a significant influence on customer satisfaction.